KEDUDUKAN HUKUM KUASA WAJIB PAJAK NON-KONSULTAN DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 7 TAHUN 2021 TENTANG HARMONISASI PERATURAN PERPAJAKAN: ANALISIS TERHADAP PERLINDUNGAN HAK DAN KEPASTIAN HUKUM WAJIB PAJAK - Wahyu Nuryanto (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2026)
The regulation of Taxpayer Power of Attorney (KWP) has undergone significant developments in line with the enactment of Law Number 7 of 2021 concerning the Harmonization of Tax Regulations (HPP Law) and Government Regulation Number 50 of 2022. This regulation expands the subject of power of attorney not only to tax consultants, but also to include other parties and specific families, with an emphasis on competence as a key prerequisite. This study aims to analyze the legal arrangements regarding the power of attorney of non-consultant taxpayers in the HPP Law and its implementing regulations, as well as examine the implications of the relaxation of power of attorney requirements on the protection of taxpayers' rights and legal certainty. The research method used is normative juridical with a legislative, conceptual, and court decision approach, especially the Constitutional Court Decision Number 63/PUU-XV/2017. The results of the study show that the legal foundation of non-consultant power of attorney has been solid and constitutionality is maintained as long as the regulation is in the technical-administrative realm. However, legal certainty has not been fully optimal due to the lack of operational competency indicators, coaching, supervision, and sanction mechanisms, thus giving rise to the potential for multiple interpretations and enforcement gaps in practice. In this context, PMK 229/PMK.03/2014 serves as an important administrative framework, but requires alignment so as not to limit the substantive rights of taxpayers and proxies. This study confirms that the effectiveness of protecting taxpayer rights is highly dependent on the accountability of the power of attorney as a tax intermediary, which must be supported by clear competency standards, consistent governance, and equal supervision.